Web-Based Electrocardiography Learning Application Development for Basic Trauma and Cardiac Life Support Training - Nur Halimah; Ni Luh Putu Inca Buntari Agustini; Ni Made Dewi Wahyunadi; I Wayan Edi Sanjana (JURNAL INFO KESEHATAN, 2026)
Electrocardiography (ECG) interpretation is an essential competency for healthcare providers, particularly nurses, in managing cardiac emergencies during Basic Trauma and Cardiac Life Support (BT&CLS). However, ECG learning in BT&CLS training is still predominantly delivered through conventional, paper-based methods, which may limit learners’ ability to rapidly and accurately interpret cardiac rhythms. Advances in web-based learning offer opportunities to enhance flexibility, interactivity, and learner engagement in emergency care education. This study aimed to develop and evaluate a web-based ECG learning application for BT&CLS training, focusing on its usability and technology acceptance. This study employed a mixed-method Research and Development (R&D) design combined with a quantitative approach. The web-based application was designed to include ECG theory modules, rhythm interpretation exercises, interactive quizzes with immediate feedback, and progress tracking features. Usability was assessed using an adapted System Usability Scale (SUS), while technology acceptance was measured using a modified Technology Acceptance Model (TAM) questionnaire. A total of 31 participants involved in BT&CLS training were recruited. Instrument reliability testing demonstrated excellent internal consistency. The results indicated high levels of user agreement across all usability dimensions, including functionality, reliability, ease of use, and portability of the application. Furthermore, all TAM components perceived usefulness, perceived ease of use, user attitude, behavioral intention, and user trust were rated in the high category. Participants reported that the application was intuitive, supportive of self-paced learning, and relevant to the competencies required in BT&CLS training. Overall usability and technology acceptance findings indicate that the web-based application effectively addresses key limitations of traditional paper-based ECG learning by enhancing flexibility, interactivity, and learner engagement in BT&CLS training. These findings suggest that digital learning tools can support self-paced practice and reinforce ECG interpretation competencies required in emergency care contexts. The developed web-based ECG learning application demonstrated strong usability and high technology acceptance among BT&CLS trainees. The application shows substantial potential to be integrated into BT&CLS training programs as a complementary learning tool, supporting flexible, interactive, and learner-centered acquisition of ECG interpretation skills. Further studies are recommended to evaluate its effectiveness in improving learning outcomes and clinical performance in emergency settings.